ChemInform Abstract: Ferrofluids: Synthetic Strategies, Stabilization, Physicochemical Features, Characterization, and Applications. Issue 52 (29th December 2014) - Joseph, Aswathy; Mathew, Suresh
Abstract Review: [387 refs.